Psychological well-being of employees of a Philippine State University in times of covid-19 pandemic - Arbiol, Jennifer M.; Gonzales, Edeliza S.; Cabajes, Angelie V. (2022)
The study explores the level of psychological well-being of employees of a Philippine State University during the pandemic.